Cis‐1, 4‐Selective Copolymerization of Ethylene and Butadiene: A Compromise between Two Mechanisms. Issue 24 (4th May 2017) - Wu, Chunji; Liu, Bo; Lin, Fei; Wang, Meiyan; Cui, Dongmei
Abstract: Introducing ethylene units into polybutadiene backbones is an approach to synthesize advanced rubber materials, which has been a research challenge because of distinct polymerization mechanisms of the two monomers. To date, only trans ‐1, 4‐ and 1, 2‐regulated copolymers have been obtained. Herein, we reported the unprecedented cis ‐1, 4 selective copolymerization of ethylene and butadiene by using the thiophene‐fused cyclopentadienyl‐ligated scandium complexes. The effects of the sterics and electronics of the catalytic precursors as well as the monomer loading mode on the activity and selectivity as well as the sequence lengths were investigated, and the mechanism was elucidated. Thus a novel ethylene‐based rubber material possessing a high molecular weight, 80 % cis ‐1, 4 regularity and a T g =−94 °C without an obvious melting point owing to short polyethylene sequences even at its content up to 45 mol %, was isolated. This new rubber material exhibited excellent anti‐flowing performance and strong tensile strength. Abstract : Copolymerization of ethylene and butadiene is a challenge because of the distinct polymerization mechanisms. A compromise was found between the two mechanisms that made possible the synthesis of a novel ethylene‐based rubber material with highly cis ‐1, 4‐regulated butadiene units and high ethylene content.